The Relationship of age, attitude, knowladge, cost to cataract surgery - Aminatul Fitria (Jurnal Berkala Epidemiologi, 2016)
A cataract is a cause of 51% of blindness in the world. Cataracts can only be cured by surgery, but most of the population with cataracts in Indonesia have not had surgery due to several factors. This will have an impact on increasing blindness cases. This study aims to determine the relationship of age, attitude, family support, and costs for actions to perform cataract operations. This study was an observational analytic study with a cross-sectional design. This research was conducted in the clinic and inpatient care at Mata Undaan Hospital Surabaya in December 2014 until June 2015. The total sample in this study was 60 respondents. Sampling using simple random sampling. Data collection is done by looking at medical records and interviews with questionnaire guidelines. Data processing using Chi-Square or Fisher's exact analysis. The results showed that there was a relationship between family support (p = 0.010), operating costs (p = 0.001) and attitude (0,000) while age was unrelated (p = 1,000), to actions for cataract surgery. The conclusion of this study is the attitude, family support, and operating costs related to actions for cataract operations, while age is not related to actions to perform cataract operations. The advice can be given is to provide information through leaflets and other media placed in the lobby of the patient's waiting room to increase patient knowledge, and counseling to the patient's family to convince patients to surgery.